(untitled) (Brazilian Journal of Behavioral and Cognitive Therapy, 2022)
Institutional care is the reality of many children and adolescents who have been removed from their family. Because they are exposed to risk factors, they are likely to have behavioral problems. Thus, the objective of the present study was to evaluate a behavior-analytic intervention for girls in institutional care. Participants were 10 institutionalized female adolescents between 12 and 17 years old of the city of Curitiba and surroundings. The intervention was evaluated using YSR, TDE II, and IEP. The intervention was composed by 15 sessions based on the Moral Behavior Program (Gomide, 2010; Gomide & Barros, 2020) for adolescents. It was observed a reduction of the behavior problems with the average effect size (d = 0.650). There was also an increase in all TDE categories. The importance of developing researches guided to institutionalized girls due to their peculiarities is highlighted. Larger sample studies are recommended.